Reviewing Mario Pratesi : The Critical Press and Its Influence - Urbancic, Anne (Book collections on Project MUSE., 2014)
An insightful history of book reviewing as a genre and a detailed study of its role in Italian literary culture, Reviewing Mario Pratesi opens up a new area for investigation within Italian literary studies.